2017
DOI: 10.4236/gsc.2017.72012
|View full text |Cite
|
Sign up to set email alerts
|

Towards Biorefinery Production of Microalgal Biofuels and Bioproducts: Production of Acetic Acid from the Fermentation of <i>Chlorella</i> sp. and <i>Tetraselmis suecica</i> Hydrolysates

Abstract: Successful commercialization of microalgal bio-industry requires the design of an integrated microalgal biorefinery system that facilitates the co-production of biofuels, high-value products and industrial chemicals from the biomass. In this study, we investigated the use of sugar hydrolysate obtained from enzy-How to cite this paper: Kassim, M.A., Rashid, M.A. and Halim, R. (2017) Towards Biorefinery Production of Microalgal Biofuels and Bioproducts: Production of Acetic Acid from the Fermentation of Chlorell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The carbohydrate productivity could be influenced by extrinsic and intrinsic factors during the cultivation period [ 46 ]. Previous reports have clearly indicated that CO 2 concentrations, temperature, pH, light intensity, salinity, and nitrogen source significantly affect the productivity capacity of microalgae [ 47 , 48 ]. It has been highlighted that both pH and CO 2 levels could be the most crucial factors [ 39 , 40 ] due to the higher formation ratio of carbonic acid in the medium when the CO 2 level increases [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The carbohydrate productivity could be influenced by extrinsic and intrinsic factors during the cultivation period [ 46 ]. Previous reports have clearly indicated that CO 2 concentrations, temperature, pH, light intensity, salinity, and nitrogen source significantly affect the productivity capacity of microalgae [ 47 , 48 ]. It has been highlighted that both pH and CO 2 levels could be the most crucial factors [ 39 , 40 ] due to the higher formation ratio of carbonic acid in the medium when the CO 2 level increases [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to determine the optimum cultivation conditions, favorable or merely tolerable for the growth of microalgal species. Cultivation under unfavorable conditions could either increase or decrease the microalgal growth and carbohydrate content [21,22]. The most common cultivation conditions such as the surrounding temperatures, light intensity, pH, and CO 2 concentration have reported that these cultivation parameters can significantly influence the microalgal growth and carbohydrate accumulation in microalgal biomass during cultivation [23].…”
Section: Strategy To Improve Microalgal Carbohydrate Accumulationmentioning
confidence: 99%
“…It is known that microalgal lipids from microalgae can be used to produce biodiesel via transesterification. Meanwhile, the carbohydrate of the microalgae can be used as reducing sugar feedstock to produce a wide range of fine chemicals through fermentation [16]. The high carbohydrate content in the T. suecica biomass exhibits potential to be used as a feedstock for biofuel or fine chemical feedstock through fermentation.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Hence, this study was designed to enhance the enzymatic hydrolysis of pretreated T. suecica biomass at high solid concentration. The marine water T. suecica was selected for this study because this microalgae species has a great potential to be used in dual application CO 2 capture and fine chemical production [16,17]. Initially, different pretreatment approaches, i.e.…”
Section: Introductionmentioning
confidence: 99%